Mortality and survivors' consumption - Michael Grimm (Verein für Socialpolitik, Ausschuss für Entwicklungsländer, 2006)
The literature suggests that in developing countries illness shocks at the household level can have a negative and severe impact on household income. Few studies have so fare examined the effects of mortality. The major difference between illness and mortality shocks is that a death of a household member does not only induce direct costs such as medical and funeral costs and possibly a loss in income, but that also the number of consumption units in the household is reduced. Studies so far focused mainly on adult mortality, disregarded the death of other household members and distinguished only insufficiently between the immediate impact, and the impact after coping strategies have been implemented. Using data for Indonesia, I show that the economic costs related to the death of children and older persons seem to be fully compensated by the decrease of consumption units in the household. In contrast, when prime-age adults die, survivors face additional costs due to the loss of income and, in consequence, implement coping strategies. These strategies are quite efficient and it seems that on average households even over-compensate their loss. This suggests that the implementation of general formal safety nets which are still absent in Indonesia?as in most developing countries?can give priority to the insurance of other types of risks, such as unemployment, illness or natural disasters.
Keywords: O12; J12; I12; D12; 330; Mortality; risk; insurance; micro-model of consumption growth; Indonesia